Legal Review of Decisions Exceeding The Demands (Ultra Petita) - Erin Irgo Septyalona; Bastianto Nugroho; Mohammad Roesli (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
The aim of this research is to determine the provisions for proceedings at the General Court and specifically the provisions for proceedings at the Constitutional Court in carrying out the judicial review of laws against the 1945 Constitution according to Law Number 24 of 2003 concerning the Constitutional Court. Method Normative research, with a conceptual approach, namely legal research that looks for principles, doctrines and sources of law in a juridical philosophical sense.Results of the Constitutional Court (MK). The establishment of the Constitutional Court was based on the third amendment to the 1945 Constitution which was carried out by the MPR in 2001. The Constitutional Court is an independent judicial authority to administer justice to uphold law and justice alongside the Supreme Court and subordinate courts (Article 24 paragraphs (1) and (2) Amendment Third). The Constitutional Court was formed to guarantee that the constitution as the highest law can be enforced, so that the Constitutional Court is known as the guardian of the constitution.